Factors Influencing the Interest of Women of Childbearing Age in Undergoing Early Detection of Cervical Cancer in the Working Area of ​​the Ome Tidore Inpatient Health Center UPT - Nurdiana Hi. Djalil; Rani Safitri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Cervical cancer remains a major cause of morbidity and mortality among women, particularly in developing countries. Although early detection methods such as visual inspection with acetic acid (IVA) and Pap smear are effective, participation among women of reproductive age is still low. Identifying factors that influence women’s interest in cervical cancer screening is essential to strengthen prevention programs at the primary healthcare level. Method: This study used a quantitative analytical observational design with a cross-sectional approach. The research was conducted in the working area of UPT Puskesmas Rawat Inap Ome Tidore. Participants were women of reproductive age (15–49 years) selected through purposive sampling. Data were collected using a structured questionnaire assessing socio-demographic characteristics, knowledge, attitudes, access to health information, family or husband support, and interest in early detection of cervical cancer. Data analysis included univariate and bivariate analysis using Chi-square or Fisher’s exact tests. Results: The results showed that age, education level, knowledge, attitudes, access to health information, and family or husband support were significantly associated with women’s interest in early detection of cervical cancer. Women aged 25–49 years, those with higher education, good knowledge, positive attitudes, adequate access to information, and strong family support demonstrated higher interest in screening. Fear, embarrassment, lack of time, and misconceptions were identified as common barriers. Conclusion: Women’s interest in cervical cancer early detection is influenced by predisposing, enabling, and reinforcing factors. Strengthening health education, improving information access, and involving family support are key to increasing screening participation.